Inhibition of soluble epoxide hydrolase by phytochemical constituents of the root bark of Ulmus davidiana var. japonica - Jang Hoon Kim; Ji Su Park; Yun Ji Lee; Sena Choi; Young Ho Kim; Seo Young Yang (Taylor & Francis Group, 2021)
A novel compound 1 and nine known compounds (2-10) were isolated by open column chromatography analysis of the root bark of Ulmus davidiana. Pure compounds (1-10) were tested in vitro to determine the inhibitory activity of the catalytic reaction of soluble epoxide hydrolase (sEH). Compounds 1, 2, 4, 6-8, and 10 had IC50 values ranging from 11.4 ± 2.3 to 36.9 ± 2.6 μM. We used molecular docking to simulate inhibitor binding of each compound and estimated the binding pose of the catalytic site of sEH. From this analysis, the compound 2 was revealed to be a potential inhibitor of sEH in vitro and in silico. Additionally, molecular dynamics (MD) study was performed to find detailed interaction signals of inhibitor 2 with enzyme. Finally, compound 2 is promising candidates for the development of a new sEH inhibitor from natural plants.